2008
DOI: 10.1002/gps.2087
|View full text |Cite
|
Sign up to set email alerts
|

Aging of cerebral white matter: a review of MRI findings

Abstract: Background-Cerebral aging is a complex and heterogeneous process that is associated with a high degree of inter-individual variability. Structural magnetic resonance imaging (MRI) can be used to identify and quantify non-disease-related aging of the cerebral white matter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
376
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 479 publications
(407 citation statements)
references
References 83 publications
28
376
2
1
Order By: Relevance
“…There existed a significant association between white matter lesion load and severity of DTI and MTR measures in the normalappearing white matter with the microstructural changes in normal brain tissue being more closely related to the patients' clinical presentation than the volume of visible white matter abnormalities [9,32,52,61,69,70,74,92,93]. These observations clearly indicate that age-related small vessel disease of the brain is a diffuse process affecting the entire brain and that white matter lesions are probably only the tip of the iceberg.…”
Section: Age-related White Matter Changes and Normal-appearing Brain mentioning
confidence: 83%
“…There existed a significant association between white matter lesion load and severity of DTI and MTR measures in the normalappearing white matter with the microstructural changes in normal brain tissue being more closely related to the patients' clinical presentation than the volume of visible white matter abnormalities [9,32,52,61,69,70,74,92,93]. These observations clearly indicate that age-related small vessel disease of the brain is a diffuse process affecting the entire brain and that white matter lesions are probably only the tip of the iceberg.…”
Section: Age-related White Matter Changes and Normal-appearing Brain mentioning
confidence: 83%
“…Consistently, higher SHBG levels were associated with lower BMI and insulin levels in our sample (Table S4). WM alterations, such as compromised microstructural integrity, volume loss, and WM lesions have been linked to aging (Gunning‐Dixon, Brickman, Cheng, & Alexopoulos, 2009) and poorer cardio‐metabolic health (Launer et al., 2015; Segura et al., 2009). In parallel, the association of higher SHBG levels with smaller GM volume may be related to SHBG's role in regulating sex‐hormone‐related mechanisms, wherein higher SHBG typically indicate lower bioavailable T and estrogen levels.…”
Section: Discussionmentioning
confidence: 99%
“…The way in which the impact of low-grade systemic inflammation on cognition is mediated is at present unclear. The known association between cognitive ageing and white matter pathology (Gunning-Dixon et al 2009) raises the possibility that a proinflammatory state could result in acceleration of white matter damage or progressive loss of white matter integrity on the basis of microvascular damage. This idea is supported by the Rotterdam Study of 1,033 dementiafree elders (aged 60-90 years) which reported a significant association between elevated CRP and the presence and 3-year progression of white matter lesions on magnetic resonance imaging (van Dijk et al 2005).…”
Section: Discussionmentioning
confidence: 99%